En kvalitativ utvärdering av det accelerometerbaserade hältdetektionssystemet "Lameness Locator" - Suneson, Ebba (SLU/Dept. of Biomedical Sciences and Veterinary Public Health (until 231231), 2009)
Background: Evaluation of lameness in horses is traditionally performed by a veterinarian who subjectively evaluates the movements of the horse. Accordingly, lameness diagnosis varies with the veterinarian and circumstances for which the horse is examined. Research within the area has long tried to establish an objective and standardized method for lamenessevaluation in horses. Several methods have been shown to be reliable and are used regularly within research, for example measurement of forces between the hoof and ground, and measurement of movements with high speed cameras or accelerometers. However these methods require considerable preparation, standardization, and expensive equipment as well as produce large amounts of data that are incomprehensible for the clinician. Consequently, up until now the implementation of objective lameness methodologies to a normal clinical setting has been prohibited.